Controlabilidade exata para sistemas de Bresse não lineares - Tumelero, Marieli Musial (2017)
This work is concerned with the exact controllability for the Bresse system. We have made three inserts in the equations that make up the system. In the first one, we add a memory term and solve boundary exact the controllability problem as well as the interior exact controllability. In the second insert, we remove the memory term, we add linear terms to the three equations and we solve the boundary exact problem controllability. And in the latter one, we replace of linear terms by asymptotically linear terms and we also establish the boundary exact controllability result. Our calculations show that a minimum time of control is necessary to guarantee the control efficiency. In the case of interior controllability, we also need a minimum region for the efficiency of such controls. The main result of each chapter is obtained by applying the Hilbert Uniqueness Method due to Lions [28, 29].